Pemahaman Makna Gereja dan Implikasinya bagi Kepemimpinan Kristen dan Orang Peraya - Perangin Angin, Yakub Hendrawan; Yeniretnowati, Tri Astuti (Pusat Studi Pentakosta Indonesia, 2023)
Many Christians still do not understand the meaning of the church properly and correctly, even worse, they do not understand the nature of the church at all, why there is a church in this world, so there are still those who believe that the church has nothing to do with them. This research is intended to provide correct understanding and implications regarding the meaning of the church according to Biblical truth for Christians, Christian leaders and church leaders. The method used in writing this article is a qualitative method with a literature research approach. The results and conclusions of this research show how much it has implications for believers, Christian leaders and church leaders when they correctly and clearly understand that a correct understanding of the meaning of the church is very important as a vision of life and the vision of the church both personally and institutionally so that it is able to proclaim God's shalom. in the world according to God's purpose for creating humans, presenting the church in the world as mandated by God to be real and effective in various aspects of life, as stated in Proverbs 29:18